Clinical features and blood iron metabolism markers in children with beta-propeller protein associated neurodegeneration. (September 2020) - Belohlavkova, Anezka; Sterbova, Katalin; Betzler, Cornelia; Burkhard, Stuve; Panzer, Axel; Wolff, Markus; Lassuthova, Petra; Vlckova, Marketa; Kyncl, Martin; Benova, Barbora; Jahodova, Alena; Kudr, Martin; et al.
Abstract: Background: Neurodegeneration with brain iron accumulation constitutes a group of rare progressive movement disorders sharing intellectual disability and neuroimaging findings as common denominators. Beta-propeller protein-associated neurodegeneration (BPAN) represents approximately 7% of the cases, and its first signs are typically epilepsy and developmental delay. We aimed to describe in detail the phenotype of BPAN with a special focus on iron metabolism. Material and methods: We present a cohort of paediatric patients with pathogenic variants of WD-Repeat Domain 45 gene ( WDR45) . The diagnosis was established by targeted panel sequencing of genes associated with epileptic encephalopathies (n = 9) or by Sanger sequencing of WDR45 (n = 1). Data on clinical characteristics, molecular-genetic findings and other performed investigations were gathered from all participating centres. Markers of iron metabolism were analysed in 6 patients. Results: Ten children (3 males, 7 females, median age 8.4 years) from five centres (Prague, Berlin, Vogtareuth, Tubingen and Cologne) were enrolled in the study. All patients manifested first symptoms (e.g. epilepsy, developmental delay) between 2 and 31 months (median 16 months). Seven patients were seizure-free (6 on antiepileptic medication, one drug-free) at the time of data collection. Neurological findings were non-specific with deep tendon hyperreflexia (n = 4) and orofacial dystonia (n = 3) being the most common. Soluble transferrin receptor/log ferritin ratio was elevated in 5/6 examined subjects; other parameters of iron metabolism were normal. Conclusion: Severity of epilepsy often gradually decreases in BPAN patients. Elevation of soluble transferrin receptor/log ferritin ratio could be another biochemical marker of the disease and should be explored by further studies. Highlights: First study focusing on potential alterations in blood iron metabolism in BPAN. Elevation of sTfr/log ferrit – possible new biochemical marker of BPAN. Gradually decreasing severity of epilepsy in some BPAN patients.